2017
DOI: 10.1177/0022487117702583
|View full text |Cite
|
Sign up to set email alerts
|

Does New Teacher Induction Really Improve Retention?

Abstract: Policymakers have increasingly worked to combat teacher turnover by implementing induction programs for early-career teachers. Yet the existing evidence for the effects of induction on turnover is mixed. Drawing on data from the three most recent administrations of the Schools and Staffing and Teacher Follow-Up Surveys, as well as the Beginning Teacher Longitudinal Study, this study investigates whether different kinds of induction supports predict teacher turnover among nationally representative samples of fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
72
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(91 citation statements)
references
References 20 publications
3
72
1
1
Order By: Relevance
“…Over the past several decades, a shortage of minority school teachers has been an issue of national importance. Numerous scholars and commentators have argued that there is a growing mismatch between the degree of racial/ethnic diversity in the nation's student population and the degree of diversity in the nation's elementary and secondary teaching force (for reviews, see Albert Shanker Institute, 2015; Quiocho & Rios, 2000;Torres et al, 2004;Villegas & Irvine 2010;Villegas & Lucas, 2004;Villegas, Strom & Lucas, 2012;Zumwalt & Craig, 2005). Typically, scholars and commentators have held that as the nation's population, and in turn the nation's student body, has grown more diverse, the teaching force has not kept pace.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past several decades, a shortage of minority school teachers has been an issue of national importance. Numerous scholars and commentators have argued that there is a growing mismatch between the degree of racial/ethnic diversity in the nation's student population and the degree of diversity in the nation's elementary and secondary teaching force (for reviews, see Albert Shanker Institute, 2015; Quiocho & Rios, 2000;Torres et al, 2004;Villegas & Irvine 2010;Villegas & Lucas, 2004;Villegas, Strom & Lucas, 2012;Zumwalt & Craig, 2005). Typically, scholars and commentators have held that as the nation's population, and in turn the nation's student body, has grown more diverse, the teaching force has not kept pace.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, scholars and commentators have held that as the nation's population, and in turn the nation's student body, has grown more diverse, the teaching force has not kept pace. Some go further-arguing that the teaching force has changed in the opposite direction, becoming even less diverse and more homogeneously White (e.g., Rogers-Ard et al, 2013;Lewis & Toldson, 2013;Villegas, Strom & Lucas, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The evidence base in relation to how teacher perceptions change from the pre‐service to the novice teacher year is limited. It is the case that in the USA there have been a number of larger‐scale longitudinal studies mainly focusing on the impact of teacher induction on teacher retention, making use of extant national survey databases (Glazerman et al ., ; Ronfeldt & McQueen, ). However, these studies focus on surveys of teachers in the first few years of teaching in schools and do not encompass data which bridges from pre‐service to in‐service phases.…”
Section: Introductionmentioning
confidence: 99%
“…In parallel, there is a second group of works that deals with professional incorporation directly, i.e., as a research object. These works -based on pioneering studies that have identified, for several decades, various stages of the teachers' professional life (FULLER, 1969;HUBERMAN, 1989;KATZ, 1972;VAN MAANEN;SCHEIN, 1979)-have multiplied exponentially in the last 15 years, addressing issues as diverse as the attraction and retention of novice teachers (LONG et al, 2012;RONFELDT;MCQUEEN, 2017), the problems and successes of novice teachers (SOLIS ZAÑARTU et al, 2016) and the link between initial training and the first professional experiences (BASTIAN; MARKS, 2017), just to name a few.…”
Section: Regarding the Study Of Professional Incorporationmentioning
confidence: 99%